Reservoir management - Pepper, A. T. (ICE Publishing, 2019)
Reservoir Management is a guide to managing all aspects of small to large reservoirs and dams. Reservoir managers now require a wealth of technical, environmental and legal knowledge alongside a background to key aspects of design, as well as safety know-how, in order to successfully manage their assets. There is also a need for reservoir managers to understand not just the technical fundamentals of reservoirs but to understand the impact they can have on the local environment.